2020
DOI: 10.1103/physrevlett.124.120603
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Entropy Production from Short Experiments

Abstract: We provide a strategy for the exact inference of the average as well as the fluctuations of the entropy production in non-equilibrium systems in the steady state, from the measurements of arbitrary current fluctuations. Our results are built upon the finite-time generalization of the thermodynamic uncertainty relation, and require only very short time series data from experiments. We illustrate our results with exact and numerical solutions for two colloidal heat engines. arXiv:1910.00476v2 [cond-mat.stat-mech] Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 56 publications
3
96
0
Order By: Relevance
“…(38), (42) as well as (45) to determine the leading orders of the scaled mean values, eqs. ( 30)- (33), their response terms, their corresponding diffusion coefficients, eqs. (A.1)-(A.4), as well as the scaled total entropy production rate (35).…”
Section: Fast Drivingmentioning
confidence: 99%
See 1 more Smart Citation
“…(38), (42) as well as (45) to determine the leading orders of the scaled mean values, eqs. ( 30)- (33), their response terms, their corresponding diffusion coefficients, eqs. (A.1)-(A.4), as well as the scaled total entropy production rate (35).…”
Section: Fast Drivingmentioning
confidence: 99%
“…( 50) for fast driving reduces to the result for steady-states in refs. [32,33] in the limit of short observation times. As a consequence, we have generalized this result to arbitrary time-dependent driving and shown that the total entropy production rate can always saturate the TUR in the short-time limit beyond steady-states for arbitrary driving.…”
Section: Observablementioning
confidence: 99%
“…The entropy production rate can be directly obtained from the system's phase-space trajectory if the underlying dynamical equations of the system are known [15][16][17][18] . This is not the case however for the vast majority of systems, such as biological systems [19][20][21] , and consequently, there has been a lot of interest in developing new methods for estimating the entropy production rate directly from trajectory data [22][23][24][25][26][27][28][29][30][31][32][33] . Some of these techniques involve the estimation of the probability distribution and currents over the phase-space 22,26 , which requires huge amounts of data.…”
mentioning
confidence: 99%
“…An alternative strategy is to set lower bounds on the entropy production rate [34][35][36][37][38] by measuring experimentally accessible quantities. One class of these bounds, for example, those based on the thermodynamic uncertainty relation (TUR) [38][39][40][41][42] , have been further developed into variational inference schemes which translate the task of identifying entropy production to an optimization problem over the space of a single projected fluctuating current in the system [26][27][28][29] . Recently a similar variational scheme using neural networks was also proposed 30 .…”
mentioning
confidence: 99%
“…In the absence of currents, potential asymmetries in the forward and reverse trajectories can still be exploited to bound the entropy production rate (29,30,50), but to our knowledge no existing method is capable of producing nonzero bounds when forward and reverse trajectories are statistically identical. Moreover, even though previous bounds can become tight in some cases (51), optimal entropy production estimators for nonequilibrium systems are in general unknown.…”
mentioning
confidence: 99%